Family Perception in Readiness Accepting Discharge Planning Determined by Nursing Advocacy Program - Mohamad Judha (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Planning for patients to go home raises the issue of whether the patient is ready to face health problems at home, the lack of a support system becomes a problem especially if the patient as the head of the family needs continuity of care both in the healing process and in maintaining the patient's health status both at home sick or at home. The purpose of this study was to determine how is the Role of Advocacy given by Nurses with Readiness in Receiving Discharge Planning by patients and families. Methods: The cross-sectional correlational study in this study views the patient's family support in readiness to receive the patient's home program on the ward. Sampling 97 respondents with a purposive sample technique. Results: Family perceptions about nurses in the positive category (73.2%). The level of family readiness in accepting return planning in the good category (53.6%), the results of the bivariate analysis using the Spearman rating relate to family perceptions about nurse advocacy with readiness in accepting return planning with a p value of 0.00 <alpha 0.01. Conclusion: Family perceptions about nurse advocacy with home preparation have a strong relationship, so family assistance in nursing care in re-care planning is needed. family perceptions of nurses are needed including nursing actions or other matters relating to care by the family also need to support patient health.